Cafeicultura de precisão: análise econômica e uso da geoestatística - Ferraz, Gabriel Araújo e Silva (2010)
Coffee is one of the major agricultural products in the Brazilian agribusiness and Brazil is the major coffee producer of the world. Every day Brazilian producers invest more in technology and practices that allow increasing the yield resulting in more gains to the producers. The precision agriculture could be a feasible alternative to reduce costs in coffee sector, because the knowledge of some soil features associated with the coffee yield response could make the located an rational application of fertilizer easer, with environmental and economical positive results. Some research have been developed aiming to characterize the variability of the soil features (chemical and physics) and the variability of the plant (leaf and fruit) in the coffee agrossystem, with different methodologies, areas and cultivars. Studies of spatial distribution of pest and disease infestation, fertilizer in variable rates and leaf fall because of the manual harvest, also have been developed. These different studies showed the precision agriculture great potential to be applied in coffee field and became an important tool of this culture development. Therefore, the aim of this work is to apply the precision agriculture technique using the geosatistics to map soil chemical attributes and map plant attributes. And also study the technical and economical feasibility of the precision agriculture in a coffee field in order to collaborate with the diffusion of this technology.